Trends in steroid agent and diluent choices for epidural steroid injections: a survey of Spine Intervention Society physicians. Issue 8 (24th May 2019) - Clements, Nathan; Vydra, Darrell; Cushman, Daniel M.; Nagpal, Ameet; Julia, Jonathan; Zheng, Patricia; McCormick, Zachary L.
Abstract : Background: Epidural steroid injections (ESIs) are a frequently used treatment for refractory radicular spinal pain. ESIs, particularly transforaminal epidural steroid injections (TFESI), may provide pain relief and delay the need for surgery. Corticosteroid agent and diluent choices are known to impact the safety of ESIs. In particular, the risk of embolization with particulate corticosteroids has led to recommendations for non-particulate steroid use by the Multisociety Pain Workgroup. Additionally, there is in vitro evidence that ropivacaine can crystalize in the presence of dexamethasone, potentially creating a particulate-like injectate. Despite widespread use and known risk mitigation strategies, current practice trends related to steroid and diluent choices are unknown. Objective: Identify the use of particulate versus non-particulate corticosteroids for epidural steroid injections in the cervical and lumbar spine, as well as local anesthetics commonly used as diluents during these procedures. Methods: Cross-sectional survey study of 314 physician members of the Spine Interventional Society. Results: 41% and 9% of providers reported using particulate corticosteroids during lumbar TFESIs and cervical TFESI, respectively. Four per cent of providers reported the use of ropivacaine in cervical TFESIs. Forty-four per cent of respondents reported using anesthetic in cervical interlaminar ESIs. 21% of providers report using high volumes (> 4.5 mL) during cervical interlaminar ESIs. Conclusion: Current trends, as assessed by this survey study, indicate substantial variability in steroid and diluent choice for ESIs. Patterns were identified that may impact patient safety including the continued use of particulate corticosteroids for TFESIs and the use of ropivacaine during TFESIs by a subset of respondents.